Pelatihan Saham Online - ARA Hunter Melalui Pemesanan IPO Bagi Ibu Rumah Tangga Bekerjasama Dengan Investara - Anggraeni, Dwi Puspita (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
Housewife with daily activities, usually get difficulties in earning income due to constraints on working outside the home. Stock investment can be one of the solutions. One way to attain maximum profit in ARA stocks with minimal risk can be achieved through transactions in newly listed stocks (IPO) in the market. With accurate and comprehensive analysis, it can be determined whether the IPO prospectus has potential for ARA or ARB. IPO stock transactions also require relatively small capital as the prices offered in IPOs are still very affordable. Through this online training, housewife can engage in remote learning and practice their knowledge. Profit results from IPO stock sales have also been experienced by participants.